Building Resilience During COVID-19: Recommendations for Adapting the DREAM Program – Live Edition to an Online-Live Hybrid Model for In-Person and Virtual Classrooms - Parrott, Julia; Armstrong, Laura L.; Watt, Emmalyne; Fabes, Robert; Timlin, Breanna (Frontiers in Psychology, 2021)
In standard times, approximately 20% of children and youth experience significant emotional, behavioural, or social challenges. During covid-19, however, over half of parents have reported mental health symptoms in their children. Specifically, depressive symptoms, anxiety, contamination obsessions, family well-being challenges, and behavioural concerns have emerged globally for children during the pandemic. Without treatment or prevention, such concerns may hinder positive development, personal life trajectory, academic success, and inhibit children from meeting their potential. A school-based resiliency program for children (DREAM) for children was developed, and the goal of this study was to collaborate with stakeholders to translate it into an online-live hybrid. Our team developed a methodology to do this based on Knowledge Translation-Integration (KTI), which incorporates stakeholder engagement throughout the entire research to action process. KTI aims to ensure that programs are acceptable, sustainable, feasible, and credible. Through collaboration with parents and school board members, qualitative themes of concerns, recommendations and validation were established, aiding in meaningful online-live translation. Even though the original program was developed for intellectually gifted children, who are at greater risk for mental health concerns, stakeholders suggested using the program for both gifted and non-gifted children, given the universal applicability of the tools, particularly during this pandemic time period when mental health promotion is most relevant. An online-live approach would allow students studying at home and those studying in the classroom to participate in the program. Broader implications of this study include critical recommendations for the development of both online-live school programs in general, as well as social-emotional literacy programs for children.